THE CONCEPT OF EDUCATION ANTHROPOLOGY - Noviani Tarigan; Firman; Riska Ahmad (Yayasan Citra Dharma Cindekia, 2021)
Anthropology of education is produced in a special and separate experiment with a systematic study of educational practice from a cultural perspective, so that anthropology concludes that school is a cultural object that becomes a schema of values ??in guiding society. However, there are times when a number of teaching methods are less effective than educational media so that it is very contrary to the data obtained in the field by anthropologists. The task of educators is not only to exploit cultural values ??but to organize them and relate them to educational thought and practice as a whole. Educational anthropology can be used as a provision for students to be cultured in the midst of their cultural community. Humans create culture and because of their culture, humans live in culture. Culture affects (builds) a person's personality. And culture influences or builds personality through enculturation or education.